2023
DOI: 10.1155/2023/9117292
|View full text |Cite
|
Sign up to set email alerts
|

Delirium with Concurrent Use of Lithium and ECT and the Safety Implications: Case Reports and Review of the Literature

Mustafa Ali,
Barikar C. Malathesh,
Seshadri Sekhar Chatterjee
et al.

Abstract: Using electroconvulsive treatment and lithium together to treat acute manic episodes is common, but the effects of combining these therapies vary according to the literature. Some studies have found severe adverse side effects, while others have found the combination of both medications safe and helpful. To investigate potential adverse side effects, this study reports on two cases where bipolar affective disorder patients developed delirium after receiving electroconvulsive therapy and lithium concurrently. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, urinary catheters and antipsychotics were associated with hyperactive delirium [ 46 ]. Finally, this study also identified other factors, like ECT [ 51 ], and the combination of lithium and ECT [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, urinary catheters and antipsychotics were associated with hyperactive delirium [ 46 ]. Finally, this study also identified other factors, like ECT [ 51 ], and the combination of lithium and ECT [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%